Clinical Leadership, Effective Communication, and Team-work Effectiveness: Mediating Role of Interprofessional Collaboration - Ester Lidia Paseki; Nofierni Nofierni; Sandra Dewi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Effective communication is essential for teamwork effectiveness in healthcare, particularly in inpatient units where patient care requires coordination among multiple professionals. Internal data from Hospital X showed that more than 50% of medical incidents in the last two years were related to miscommunication among healthcare workers. In addition, the 2024 employee satisfaction survey reported that workplace communication satisfaction was only 62%, below the hospital target of 75%. This study aimed to examine the influence of effective communication on teamwork effectiveness with interprofessional collaboration as an intervening variable at Hospital X.This study used a quantitative cross-sectional design involving 226 healthcare workers, including doctors, nurses, and medical support staff. Data were analyzed using the Three-Box Method and PLS-SEM. The findings revealed that effective communication significantly influenced teamwork effectiveness both directly and indirectly through interprofessional collaboration. Interprofessional collaboration also acted as a significant mediating variable between communication and teamwork effectiveness. These results indicate that communication is a key foundation for strengthening collaboration and improving teamwork in hospitals. Therefore, hospitals should enhance communication training and interprofessional collaboration programs to improve healthcare quality and patient safety